Lidocaine-Prilocaine Cream as Analgesia for IUD Insertion: A Prospective, Randomized, Controlled, Triple Blinded Study - Tavakolian, Samira (Glob J Health Sci, 2015)
INTRODUCTION: Copper IUD is a long term and reversible contraception which equals tubal ligation in terms of sterilization. One of the barriers to using this contraception method is the fear and the pain associated with its insertion. Eutectic mixture of local anesthetics (EMLA) 5% is a local anesthetic that contains 25 mg lidocaine and 25 mg of prilocaine per gram. Application of topical analgesic cream to the cervix for laser surgery, hysteroscopy and hysterosalpingography is known AIMS: this study aimed to determine the effect of EMLA on IUD insertion pain. METHODS: This triple blind clinical trial was conducted on 92 women in a clinic in Hamedan in 2012. After applying the cream on the cervix, pain in three steps, after using Tenaculum, after inserting hystrometr and after inserting IUD and removing IUD insertion tube were assessed with visual analog scale and were compared in EMLA group and placebo group Statistical analysis used to determine and compare the pain of independent t tests, Mann-Whitney U test and repeated measures analysis of variance and chi-square tests to determine the homogeneity of variables and Fisher’s exact test was used RESULTS: Insertion hystrometr was determined as the most painful IUD insertion. The mean pain at step 2 (inserting hystrometr) was (3/11±2/53) in EMLA group, (5/23±2/31) in placebo group. EMLA cream significantly reduced the pain after using tenaculum (P<0/001), pain inserting Hystrometr (P< 0/001) and pain at IUD insertion and removing insertion tube (P< 0/001) CONCLUSIONS: Topical Application of EMLA 5% cream as a topical anesthetic on the cervix before insertion IUD reduced the pain during this procedure.